Answer:
no
Step-by-step explanation:
no enough info
Answer:
The c intercept is 42
The t intercepts are: 6, -1 and 7
Step-by-step explanation:
Given
![c(t) = (t - 6)(t +1)(t-7)](https://tex.z-dn.net/?f=c%28t%29%20%3D%20%28t%20-%206%29%28t%20%2B1%29%28t-7%29)
Solving (a): The c intercept
Simply set t to 0
![c(t) = (t - 6)(t +1)(t-7)](https://tex.z-dn.net/?f=c%28t%29%20%3D%20%28t%20-%206%29%28t%20%2B1%29%28t-7%29)
![c(0) = (0 - 6)(0 +1)(0-7)](https://tex.z-dn.net/?f=c%280%29%20%3D%20%280%20-%206%29%280%20%2B1%29%280-7%29)
![c(0) = (- 6)(1)(-7)](https://tex.z-dn.net/?f=c%280%29%20%3D%20%28-%206%29%281%29%28-7%29)
![c(0) = 42](https://tex.z-dn.net/?f=c%280%29%20%3D%2042)
Solving (b): The t intercept
Simply set c(t) to 0
![c(t) = (t - 6)(t +1)(t-7)](https://tex.z-dn.net/?f=c%28t%29%20%3D%20%28t%20-%206%29%28t%20%2B1%29%28t-7%29)
![(t - 6)(t +1)(t-7) = 0](https://tex.z-dn.net/?f=%28t%20-%206%29%28t%20%2B1%29%28t-7%29%20%3D%200)
Split
![t - 6= 0,\ \ t +1= 0,\ \ t-7 = 0](https://tex.z-dn.net/?f=t%20-%206%3D%200%2C%5C%20%5C%20t%20%2B1%3D%200%2C%5C%20%5C%20t-7%20%3D%200)
Solve for t
![t = 6,\ \ t =-1,\ \ t=7](https://tex.z-dn.net/?f=t%20%3D%206%2C%5C%20%5C%20t%20%3D-1%2C%5C%20%5C%20t%3D7)